1999
DOI: 10.1046/j.1365-2680.1999.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cyclic GMP‐dependent mechanism in the nitrergic relaxation of the bovine oesophageal groove

Abstract: 1. The present study was designed to investigate the mechanisms involved in the relaxations to nitric oxide (NO) of bovine oesophageal groove preparations suspended in organ baths for isometric tension recordings. In preparations treated with guanethidine (10(-5) M) and atropine (10(-7) M) to block adrenergic neurotransmission and muscarinic receptors, respectively, NO released from nitrergic nerves by electrical field stimulation (EFS, 0.5-16 Hz, 1 ms duration, 20 s trains) and exogenously applied as an acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The inhibitory pathway of the oesophagus involves the synthesis and release of NO by central neurones within the vagal nuclei in the brain stem and peripheral neurones in the myenteric plexus 2 . The effect of NO is mediated by cGMP 11–16 . In this study we investigated the effect of sildenafil, a drug that increases intracellular cGMP, on oesophageal motor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory pathway of the oesophagus involves the synthesis and release of NO by central neurones within the vagal nuclei in the brain stem and peripheral neurones in the myenteric plexus 2 . The effect of NO is mediated by cGMP 11–16 . In this study we investigated the effect of sildenafil, a drug that increases intracellular cGMP, on oesophageal motor function.…”
Section: Discussionmentioning
confidence: 99%
“…In the oesophagus, NO provokes hyperpolarization of the circular smooth muscle, which regulates the progression of peristaltic contractions 3–6 and relaxes the LOS 7–10 . The effect of nitric oxide is mediated by an increase in content of cyclic guanine monophosphate (cGMP), an intracellular messenger that relaxes smooth muscle 11–16 . Cyclic GMP is broken down rapidly by phosphodiesterase‐5.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors concluded that nNOS rather than eNOS is the enzymatic source of NO. Cyclic GMP is involved in the NO-mediated relaxation in canine (Daniel et al, 2002) and bovine LES (Barahona et al, 1999). Histological studies have demonstrated the presence of neurons containing nNOS or NADPH diaphorase and costaining for VIP and galanin in the human (Singaram et al, 1994), cat (Ny et al, 1995), monkey (Rodrigo et al, 1998), guinea pig (Morikawa and Komuro, 1998), bovine (Vittoria et al, 2000), and porcine esophagus (Wu et al, 2003).…”
Section: A Esophagusmentioning
confidence: 99%